A Neo-Confucian Definition of the Relationship between Individuals and Community in the Song–Ming Period (960–1644): Start with the Discovery of Multifaceted Individuals - Meihong Zhang (Religions, 2022)
Alasdair MacIntyre doubts that Confucianism can discuss the relationship between individuals and community because he maintains that it is impossible to discuss the topic in depth without a Western conception of individual rights. In this article, I show that Neo-Confucianism pays extensive attention to the relationship between individuals and community by working through several Chinese thinkers’ theories from the 11th to the 17th centuries. Neo-Confucianism seems to be focused on the exploration of the common principles of a community, but its real intention is ensuring the fundamentality of individual selves and making up for limitations caused by an excess of individual limitations. Thus, a new relationship is formed between individuals and community; that is, all individuals are equal and the common principles of community are independent of any individual. In order to make each individual harmonize with common principles, some mainstream Neo-Confucian thinkers attached great importance to the effort (gongfu 工夫) of “eliminating personal desires” (qu renyu 去人欲) since they thought that personal desires represented a selfish appeal that contradicts common principles. Influenced by this line of thinking, Neo-Confucianism fell into the predicament where individuals were suppressed, but this shortcoming was corrected in its later stage by defending the right to satisfy individual desires for survival. This study shows that Neo-Confucian discourse has given much thought to the problem of the relationship between individuals and community.